PENGARUH MEDIA SOSIAL SEBAGAI DIGITAL MARKETING TERHADAP PENGUATAN BRAND AWARENESS PADA UMKM SALAD ALVI - Nur, Safirah Wardatin; Hermawan, Haris; Winahyu, Pawestri (Relawan Jurnal Indonesia, 2023)
The rapid development of technology and communication through social media such as digital marketing is the pillar of information. Basically productive economic businesses still need the right marketing media to promote their products. Many businessmen use existing social media as a tool to promote their products to the public. One of them such as UMKM Salad Alvi which started selling their products via Instagram, Facebook, and WhatsApp. This proves the ability of UMKM Salad Alvi to adapt along with technological developments. This UMKM has used various social media such as WhatsApp, Facebook, and Instagram which can introduce brands and make it easier for consumers to choose a variety of products and quality. the use of social media can make it easier for the customer to know the existence of the UMKM. UMKM Salad Alvi, to encourage purchases and increase brand awareness or brand awareness of UMKM Salad Alvi. The purpose of this study was to determine the effect of social media WhatsApp, Facebook, and Instagram on strengthening brand awareness in MSME Salad Alvi. Quantitative method used in this research. This research involves UMKM Alvi Salad consumers who follow or transact with UMKM Alvi Salad through social media WhatsApp, Facebook, and Instagram. Regarding sampling by purposive sampling as many as 90 respondents. The results showed that the use of WhatsApp, Facebook, and Instagram social media had a significant influence on strengthening brand awareness in MSME Salad Alvi.